2016
DOI: 10.1111/ajt.13586
|View full text |Cite
|
Sign up to set email alerts
|

Early Liver Transplantation for Severe Alcoholic Hepatitis in the United States—A Single-Center Experience

Abstract: Early liver transplantation (LT) in European centers reportedly improved survival in patients with severe alcoholic hepatitis (AH) not responding to medical therapy. Our aim was to determine if a strategy of early LT for severe AH could be applied successfully in the United States. We reviewed 111 patients with severe AH at our center from January 2012 to January 2015. The primary end point was mortality at 6 months or early LT, with a secondary end point of alcohol relapse after LT. Survival was compared betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
207
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(229 citation statements)
references
References 51 publications
10
207
0
4
Order By: Relevance
“…One-year relapse rates range from 67 to 81%(69) in patients with alcoholic liver disease therefore, effective, ongoing rehabilitation for alcohol addiction is necessary to achieve sustained abstinence(70). Of note, liver transplantation without the 6-month abstinence requirement has been used to treat patients with severe, acute alcoholic hepatitis who fail to respond to steroid therapy(71, 72). Liver transplantation in this population results in long-term survival benefits with recidivism to drinking at rates comparable or below those liver transplant patients who were required to have 6 months abstinence.…”
Section: Treatment For Alcohol Use Disorder In Patients With Alcoholimentioning
confidence: 99%
“…One-year relapse rates range from 67 to 81%(69) in patients with alcoholic liver disease therefore, effective, ongoing rehabilitation for alcohol addiction is necessary to achieve sustained abstinence(70). Of note, liver transplantation without the 6-month abstinence requirement has been used to treat patients with severe, acute alcoholic hepatitis who fail to respond to steroid therapy(71, 72). Liver transplantation in this population results in long-term survival benefits with recidivism to drinking at rates comparable or below those liver transplant patients who were required to have 6 months abstinence.…”
Section: Treatment For Alcohol Use Disorder In Patients With Alcoholimentioning
confidence: 99%
“…Compared to 85 severe AH patients not responding to corticosteroids and ineligible for early LT, patients receiving salvage LT had better six months survival (89 vs. 11%, P<0.001). (Im et al, 2016) Benefit of liver transplantation was also shown in a population-based study using the United Network of Organ Sharing database in the US. The study showed that the outcomes of AH patients are similar to transplant recipients for alcoholic cirrhosis.…”
Section: Resultsmentioning
confidence: 87%
“…(Hasanin et al, 2015) Recidivism after liver transplantation for AH in all these four studies was similar to recidivism after transplantation for alcoholic cirrhosis. (Mathurin et al, 2011a, Singal et al, 2012a, Hasanin et al, 2015, Im et al, 2016) Common barriers to liver transplantation in AH include socio-cultural factors, public opinion that alcohol is in itself a self- inflicted disease, and shortage of donor organs. (Hasanin et al, 2015) However, if used for select severe AH patients, this approach would not consume more than 1–3% of the liver donor pool.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data have been confirmed in a similar, albeit single-center, prospective evaluation of rescue LT in severe AH carried out in New York. 44 In summary, these pilot studies, along with retrospective analysis of LT in patients found to have AH, 45,46 support future evaluation of LT in a carefully selected subgroup of patients with severe AH failing to respond to medical therapy, despite the fact that early LT in such patients contravenes the 6-month abstinence rule. Future studies should clarify the methods of selection for LT, maintenance of addiction health both before and after LT, in addition to patient and graft survivals.…”
Section: Alcoholic Hepatitis and Ltmentioning
confidence: 86%